INNOVATIVE DEVELOPMENT OF PRODUCTION AND IMPROVEMENT OF THE CONTROL SYSTEM OF DUAL USE GOODS (TECHNOLOGIES) (INNOVATIVE ECONOMY, 2024)
Voloshchuk K.B., Voloshchuk V.R. INNOVATIVE DEVELOPMENT OF PRODUCTION AND IMPROVEMENT OF THE CONTROL SYSTEM OF DUAL USE GOODS (TECHNOLOGIES) Purpose. The aim of the article is to study deeply the theoretical aspects and substantiate the strategic guidelines for the innovative development of the production of world-class military-tech products and improvement of the control system of dual-use goods (technologies) necessary for increasing the country's defence capabilities and achieving victory and restoring the economy.Methodology of research. General scientific and special methods were used in the research process, in particular: induction and deduction – at the stage of collecting, systematizing and processing the necessary information; analysis and synthesis – when combining the components of innovative development of production and improvement of the control system of dual-use goods (technologies); dialectical – when learning the content and essence of innovative development of production and improvement of the control system of dual-use goods (technologies); monographic – when studying the scientific experience of innovative development of production and improvement of the control system of dual-use goods (technologies); abstract and logical – when forming theoretical conclusions and proposals on the topic of research.Findings. A generalization of the theoretical aspects of the concept of innovation, the understanding of the state and the innovation index as future growth, driven by production innovations and approaches to the policy of forming export control in EU countries and improving the system of state control of dual-use goods (technologies) with the aim of expanding the opportunities of the port for the development of the domestic military industry, has been carried out.It was found that innovative results in Ukraine are better compared to the level of innovative investments, which confirms the relevance of further innovative development of the production of dual-use goods (technologies) and the recovery of the economy, and therefore, in the future, the focus should be on economic and social impact, that is, the criteria for success along with quantity and scale, there will be quality and value dimensions.The necessity of localization of the development of the production of military products was proven and the real possibility of developing innovative world-class military-tech products was confirmed by stimulating Ukrainian companies that can produce and test their products directly when using them in the process of conducting hostilities. This will make Ukraine more independent in terms of armaments and will contribute to the recovery of the economy.The expediency of long-term decisions and the transition from situational to strategic planning and state regulation of the purchase of weapons from domestic manufacturers and the development of innovative world-class military products, the expansion of international cooperation by foreign manufacturers are substantiated, which will contribute to the strengthening of the competitive positions of enterprises of the domestic defence complex.It has been established that the Government's simplification of the procedures for importing a number of dual-use goods without export control will contribute to increasing import opportunities, expanding the range of importers and the list of dual-use goods, and improving the supply of the Armed Forces at the front and supplying Ukrainian manufacturers of modern weapons.Originality. The interpretation of the understanding of innovative development as a future growth driven by innovations in the production of dual-use goods (technologies), the development of world-class innovative military-tech products, and the deregulation of the import of dual-use goods for import into Ukraine without export control procedures, which is a guarantee of security not only business, and the national and welfare of states.Practical value. Ways to solve the problems of production and foreign economic activity on the basis of innovative development of domestic production thanks to liberalization, reform, taxation, procurement regulation and export insurance are proposed; the opening of European markets for Ukrainian goods through the so-called economic “visa-free” and the expansion of import opportunities through the addition of the list of dual-use goods for import into Ukraine without export control procedures, necessary to increase the country's defence capabilities and restore the economy.Key words: dual-use goods (technologies), global innovation index, innovative products, military-tech, long-term planning, strategic orientations, control, regulation, deregulation, export, import, partners, security, economy.
Keywords: dual-use goods (technologies); global innovation index; innovative products; military-tech; long-term planning; strategic orientations; control; regulation; deregulation; export; import; partners; security; economy.